The rhetorical structure of research article abstracts in science education journal - Lia Pratiwi; Safnil Arsyad (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
The significance of reading the abstracts of research publications in particular disciplines is becoming more widely acknowledged in literature. In a scientific publication, the abstract is the second mini-text the reader may encounter after the title. The term paper's value is thus determined by its abstract, which also rates it as good or confusing. Today's contrast studies look into scientific fields' abstract rhetorical structures. It follows Hyland's (2000) model for rhetorical organization, which includes an introduction, purpose, method, product, and conclusion. The objective data for analysis is a corpus of forty abstracts from the sciences (biology, chemistry, physics, and science) that were published between 2021 and 2022. The findings revealed rhetorical variances in the four disciplines' abstract constructions of science education. In parts M1, M2, M3, and M4, this abstract follows a non-hierarchical five-motion structure with four stable movements. The research results support the idea that writers' preferred rhetorical and writing patterns in academic writing are influenced by standards regarding word counts and discourse communities. The conclusion of the research is that the arrangement of the movements found in the abstract demonstrates how useless lengthy texts are to the growth of rhetorical movements. Despite the fact that the five movements are not widely used in works, the findings show that abstract rhetorical movement patterns within JIPI groups generally mirror conventions.